2019
DOI: 10.1016/s2213-2600(18)30418-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with allogeneic mesenchymal stromal cells for moderate to severe acute respiratory distress syndrome (START study): a randomised phase 2a safety trial

Abstract: Background-Treatment with bone-marrow-derived mesenchymal stromal cells (MSCs) has shown benefits in preclinical models of acute respiratory distress syndrome (ARDS). Safety has not been established for administration of MSCs in critically ill patients with ARDS. We did a phase 2a trial to assess safety after administration of MSCs to patients with moderate to severe ARDS.Methods-We did a prospective, double-blind, multicentre, randomised trial to assess treatment with one intravenous dose of MSCs compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
517
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 491 publications
(551 citation statements)
references
References 32 publications
7
517
0
6
Order By: Relevance
“…Ahn and the colleagues had demonstrated that intratracheal transplantation of allogeneic hUCB‐derived mesenchymal stem cells (MSCs) is safe, feasible, and effective in preterm infants at high risk for BPD . Matthay and team showed that IV allogeneic BM‐MSCs was safe in adults with ARDS . Compared with other stem cell types in cord blood, MSCs are more attractive to researchers, as it is non‐immunogenic and can be expanded rapidly ex vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahn and the colleagues had demonstrated that intratracheal transplantation of allogeneic hUCB‐derived mesenchymal stem cells (MSCs) is safe, feasible, and effective in preterm infants at high risk for BPD . Matthay and team showed that IV allogeneic BM‐MSCs was safe in adults with ARDS . Compared with other stem cell types in cord blood, MSCs are more attractive to researchers, as it is non‐immunogenic and can be expanded rapidly ex vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other stem cell types in cord blood, MSCs are more attractive to researchers, as it is non‐immunogenic and can be expanded rapidly ex vivo . With these properties, allogeneic transplantation of MSCs are used for treatment of diseases in adult and neonates . ACBMNC, as a convenient source of MSC, has never been studied in prevention or treatment of BPD in preterm.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, data from a Phase2a trial in ARDS due to other etiologies reported no significant infusional toxicities or other safety issues other than the death of one patient 24h after MSC infusion, which was judged to be unrelated to cell administration. [6] With respect to clinical efficacy results to date are ambiguous. For example, the Phase2a ARDS START trial reported a trend toward higher mortality in the MSC vs. placebo arm that was attributed to patient randomization, [6] and results from a Phase1/2 trial of MSC administration in ARDS sponsored by Athersys is awaiting publication.…”
Section: Resultsmentioning
confidence: 99%
“…[6] With respect to clinical efficacy results to date are ambiguous. For example, the Phase2a ARDS START trial reported a trend toward higher mortality in the MSC vs. placebo arm that was attributed to patient randomization, [6] and results from a Phase1/2 trial of MSC administration in ARDS sponsored by Athersys is awaiting publication. One significant unresolved issue in this respect is which COVID-19 patient population to target.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation